Knowledge, attitudes and practice of healthcare providers regarding contraceptive use in adolescence in Mahalapye, Botswana - S. T. Tshitenge; K. Nlisi; V. Setlhare; R. Ogundipe (South African Family Practice, 2018)
Introduction: Adolescent pregnancy is a global public health problem, for which healthcare providers (HCPs) play a critical role to prevent unintended pregnancy. This study investigated the knowledge, attitude and practice (KAP) of HCPs towards the use of contraceptives in adolescents. Results: Of the 101 eligible for the study, 79.2% HCPs from the selected clinics and hospital responded. The majority (91.2%) of respondents felt confident to explain to adolescents how to use old contraceptive methods such as oral contraceptives or IUCD, less than half of the respondents (41.3%) were confident to explain how to use new contraceptive methods such as transdermal contraceptive patches or vaginal rings. Medical doctors felt more confident to prescribe new contraceptive methods compared with nurses, both vaginal rings (p-value = 0.0006) and transdermal contraceptive patches (p-value = 0.0003). More than two-thirds of the respondents disagreed that beliefs influenced their ability to offer contraceptive services to adolescents, half of the respondents strongly disagreed that it was morally wrong for adolescents to use contraceptives. Although three-quarters of respondents strongly agreed (median = 5, [IQR 5–6]) that they were comfortable with prescribing contraceptives to adolescents, only 23% of the respondents very much prescribed or always prescribed contraceptives to adolescents. Conclusion: Most of the HCPs prescribed contraceptives irregularly, and had limited knowledge about newer methods. To change HCPs’ KAP, in addition to continuing medical education (CME), the establishment of family planning clinics for adolescents and more undergraduate contraceptive teaching for medical and nursing students could result in the increased utilisation of contraceptive services by adolescents.